FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN STUNTING PADA BALITA DI WILAYAH KERJA PUSKESMAS TINUMBALA KELURAHAN PATETEN SATU KOTA BITUNG - Dawid, Nivantri Delia; Bawiling, Nancy S.; Munthe, Deviana P. (Yayasan Syalom Cipta Sumikolah, 2024)
Background: By definition, stunting is a condition where toddlers have less length or height when compared to age. This condition is measured by length or height that is more than mines two standard deviations of the WHO median child growth standards. Malnutrition occurs since the baby is in the womb and in the early days of birth, but stunting only appears after the child is 2 years old. A preliminary survey conducted by researchers based on stunting data provided by nutrition officers at Puskesmas Tinombala found that the number of stunting cases in Pateten Satu Village, Bitung City, taken from January to October 2023 was 115 cases. The existence of stunting cases at the research site because there are several risk factors that are obtained at the research site, which include a lack of level of maternal knowledge about the incidence of stunting, inadequate parenting, family income, sanitation, lack of awareness of mothers to bring their toddlers to health services. Objective: To determine the factors associated with the incidence of stunting in toddlers in the Tinumbala Health Center Working Area, Pateten Satu Village, Bitung City. Methodology: This research is a quantitative approach that uses descriptive research methods and survey approaches. Researchers used the Cross Sectional method which was conducted in December 2023. Sampling using total sampling technique or as a whole from the total population. Data analysis was carried out univariate, bivariate (chi square test). Results: The results of the chi square test showed the level of education p = 0.001 (<0.005), family income per month p = 0.000 (<0.005), history of LBW p = 0.005 (<0.005), history of exclusive breastfeeding p = 0. 001 (<0.005), feeding pattern p = 0.000 (<0.005), sanitation p = 0.004 (<0.005), history of infectious disease p = 0.004 (<0.005), health services p = 0.087 (<0.005). Conclusion: Factors associated with the incidence of stunting in toddlers in the Tinumbala Puskesmas Working Area, Pateten Satu Village, Bitung City are factors of education level, monthly family income, history of LBW, history of exclusive breastfeeding, feeding patterns, sanitation, history of infectious diseases, and there is no significant relationship between health services. The incidence of stunting.